The academic adaptation of Southeast Asian international students in Chinese universities - Shen, Ling; Luo, Ailing (Frontiers in Psychology, 2025)
Employing questionnaire surveys and interviews, it has been determined that Southeast Asian students generally exhibit a moderate degree of academic adaptation. They are well - adapted in terms of instructional quality, learning capabilities, school governance, educational milieu, social interactions, and Chinese language proficiency. Factors including adaptation, nationality, student status, Chinese language competence, psychological state, learning attitudes, approaches, motivation, and abilities are of significance. Instructional quality, educational environment, school governance, and social relationships also play a role in the academic adaptation of international students. Consequently, the academic adaptation of international students can be enhanced by offering specialized psychological counseling services, establishing peer support systems, strictly implementing language proficiency evaluations, upgrading teaching facilities, and strengthening the management of international students.